Transitioning to remote teams in principles of marketing: An exploratory psychometric assessment of team role effects on face-to-face and online team performance. Issue 6 (18th August 2022) - DeLong, Debbie; Vander Schee, Brian A.
Abstract: Marketing programs rely heavily on team projects to foster team performance, however hiring managers continue to note deficiencies in marketing graduates. At the same time, global health concerns accelerate the transition to remote work settings. This exploratory study extends Belbins work on team roles using a novel psychometric assessment of discrete role types. Results suggest unique performance effects associated with certain roles and role combinations that vary F2F and online. Namely, sharing primary role information and dispersing action-oriented students among online groups can optimize team performance. In contrast, F2F teams benefit from both action orientation and role dominance.